Modeling and measurement of microwave propagation multipath channels in drill pipe bore. Issue 3 (28th September 2018) - Xia, Wenhe; Guan, Wenting; Jiang, Zujun; Meng, Yingfeng; Tang, Bo
Abstract: In this paper, the characteristics of microwave propagation channels in drill pipe bore are analyzed by regarding the drill pipe as an irregular lossy cylindrical waveguide. An attenuation law is modeled using multipath propagation theory and an experimental statistical method. It is shown from physical measurement results that 5″ and $5^{1/2 ′ ′} $ drill pipe bores, widely applied in the field of air drilling, can be used as 2.4 GHz band microwave channels with the caveat that the numerous reflective surfaces in the joint section of the drill pipe produce a great deal of reflected waves. Hence, the drill pipe bore has the characteristics of a dual cluster multipath channel, and multipath fading and delay are the primary factors affecting propagation quality. The study's constructed microwave attenuation model, based on multipath channels, can be regarded as the average attenuation of the unit length in the drill pipe bore, and can be used as the basis for simulation and analysis of the longer drill pipe string. In addition, a large delay between the two clusters leads to a significant increase of the root mean square delay spread. Consequently, multipath fading and delay are the main factors affecting the channel transmission rate.